Intergovernmental cooperation rational choices in federal systems and beyond - Bolleyer, Nicole (Oxford : Oxford University Press, 2009)
This text argues that governments' choices in favour or against strong intergovernmental institutions are not primarily driven by considerations of efficiency but by internal political dynamics within their own boundaries. It applies the argument to Canada, Switzerland, the United States, and finally to the European Union.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Federal government; Intergovernmental cooperation; Central-local government relations; Federal government -- Case studies; Intergovernmental cooperation -- Case studies; Central-local government relations -- Case studies